Fracture characterisation of float glass under static and dynamic loading*. Issue 4 (1st December 2016) - Nyounguè, A.; Bouzid, S.; Dossou, E.; Azari, Z.
Abstract: This paper presents the study of float glass fracture under static and dynamic loading, with the use of experimental and numerical fracture mechanics methods. It has been shown that the value of notch fracture toughness under static loading depends neither on the kind of test nor on specimen geometry. This makes it possible to replace the three-points-bending specimens with the Brazilian discs which are, under certain test conditions, simpler and convenient to study. For both types of specimens, an analysis of the fracture strength, the notch stress intensity factor and fragmentation of specimens was carried out.